Expression of the atrial natriuretic peptide gene in the cardiac muscle of rat extrapulmonary and intrapulmonary veins. Issue 1 (January 1988) - Springall, D R; Bhatnagar, M; Wharton, J; Hamid, Q; Gulbenkian, S; Hedges, M; Meleagros, L; Bloom, S R; Polak, J M
Abstract : Atrial natriuretic peptide is a peptide regulating salt and water balance, originally isolated from the cardiac atrium, where it is synthesised as part of a precursor molecule in specialised myocardial cells. The myocardium extends into the extrapulmonary part of the pulmonary veins in many species, including man. In some small mammals, however, such as the rat, mouse, and bat, it extends further to veins in the peripheral parts of the lung. Since this myocardial layer is continuous with that in the atrium, we have looked for the possible expression of the atrial natriuretic peptide gene in this tissue in rats. Strong immunoreactivity was seen for both the peptide and the N terminal sequence (cardiodilatin) of its precursor in extrapulmonary veins and in intrapulmonary veins extending into the lung as far as the second branching point, where it was localised in the dense cored granules by electron microscopy; in situ hybridisation showed atrial natriuretic peptide messenger RNA at identical sites. Chromatography and radioimmunoassay of extracts of extrapulmonary and intrapulmonary veins showed most of the atrial natriuretic peptide immunoreactivity to be in the uncleaved (precursor molecule) form. Thus the peptide is synthesised in veins both outside and inside the lung, and these extra-atrial sites may be an important additional source of circulating atrial natriuretic peptide.